Correction: Early life-history dynamics of Pacific istiophorid billfishes: a synthesis and analysis of larval ecology, habitat, and survival - Michael K. Musyl; Lianne M. McNaughton; Yanli Jia; Robert L. Humphreys; Rob Kramer (Reviews in Fish Biology and Fisheries, 2026)

Early life-history dynamics of Pacific istiophorid billfishes: a synthesis and analysis of larval ecology, habitat, and survival - Michael K. Musyl; Lianne M. McNaughton; Yanli Jia; Robert L. Humphreys; Rob Kramer (Reviews in Fish Biology and Fisheries, 2026)

Closing the plastic budget equation in fluvial systems: A review of monitoring methods - Ana Todorova; Robert K. Niven; Matthias Kramer (Science of The Total Environment, 2026)

In-situ formation of glyphosate and AMPA in activated sludge from phosphonates used as antiscalants and bleach stabilizers in households and industry - L. Engelbart; S. Bieger; K. Thompson; L. Fischer; T. Bader; M. Kramer; S.B. Haderlein; A.M. Röhnelt; P.R. Martin; D. Buchner; R. Bloch; H. Rügner; et al. (Water Research, 2025)

Enhancing groundwater vulnerability assessment through Bayesian inference - Nasrin Taghavi; Robert K. Niven; Matthias Kramer; David J. Paull (Journal of Hydrology, 2025)

Ecomorphology in Kenya's Koobi Fora Formation: Reconstructing Early Pleistocene hominin paleoenvironments with 3D geometric morphometric analyses of bovid metapodials - Megan Malherbe; Nicole Webb; Magdalena Palisson-Kramer; Emmanuel K. Ndiema; David R. Braun; Martin Haeusler; Frances Forrest (Journal of Human Evolution, 2025)

Parasite‐Mediated Competition Limits Dominant Cervid Competitor - Jennifer A. Grauer; Joshua P. Twining; Manigandan Lejeune; Jacqueline L. Frair; Krysten L. Schuler; David W. Kramer; Angela K. Fuller (Ecology Letters, 2025)
Species interactions structure ecological communities through direct and indirect pathways with ecosystem‐wide implications. Despite mounting interest in the importance of indirect interactions, empirical evidence remains limited. Here, we demonstrate the critical role of parasite‐mediated competition in driving community outcomes in a multi‐species system of conservation and management concern. We leveraged 2 years of detection/non‐detection data of moose ( Alces alces ) and white‐tailed deer ( Odocoileus virginianus ) and parasite loads in faecal samples within a hierarchical abundance‐mediated interaction model to test hypotheses regarding interactions between these cervids and their shared parasites ( Parelaphostrongylus tenuis , Fascioloides magna ). We demonstrate that moose occupancy was limited by parasite‐mediated competition, with no evidence of population‐level effects of direct competitive interactions between moose and white‐tailed deer. Such evidence of the importance of indirect interactions and resulting community outcomes is critical for species conservation and managing range contractions due to increasing pressures from habitat loss, disease and climate change.

Survival of Eurasian lynx in the human‐dominated landscape of Europe - J. Premier; M. L. Bastianelli; J. Oeser; O. Anders; H. Andren; M. Aronsson; G. Bagrade; E. Belotti; C. Breitenmoser‐Würsten; L. Bufka; R. Černe; J. Červený; et al. (Conservation Biology, 2025)
Survival and cause‐specific mortality rates are vital for evidence‐based population forecasting and conservation, particularly for large carnivores, whose populations are often vulnerable to human‐caused mortalities. It is therefore important to know the relationship between anthropogenic and natural mortality causes to evaluate whether they are additive or compensatory. Further, the relation between survival and environmental covariates could reveal whether specific landscape characteristics influence demographic performance. We used telemetry data on 681 Eurasian lynx ( Lynx lynx ), a model apex predator with large spatial requirements, that were tracked across their European distribution. Through time‐to‐event analyses, we sought to determine the variables associated with differences in their survival. Illegal killing was the main cause of mortality (33.8%), and mortality rates were similar in protected and hunted populations (8.6% and 7.0% per year, respectively). Survival varied greatly across populations (70–95% per year). Across all study sites, higher hunting and anthropogenic mortality rates were partially compensated by lower rates of other mortality causes but not by natural mortality alone. Variation in survival depended on sex (female survival was 1.5 times greater than male survival) and seasonality (highest risk during hunting season and winter), and lower survival rates were correlated with higher human modification of landscapes at both coarse (home range composition) and fine (habitat use within home range) scales. Some variation in survival was driven by unobserved factors, which, given the high rates of human‐caused mortalities, including illegal killing, are of foremost concern. Due to the low natural mortality rates in protected and hunted populations, we conclude that anthropogenic causes of mortality are likely close to additive, such that maintaining or increasing refuge habitat with little human disturbance is critical to lynx conservation.

Numerical plastic transport modelling in fluvial systems: Review and formulation of boundary conditions - Charuni Wickramarachchi; Robert K. Niven; Matthias Kramer (Water Research, 2025)

Temperature Drives Seagrass Recovery Across the Western North Atlantic - Fee O. H. Smulders; Justin E. Campbell; Andrew H. Altieri; Anna R. Armitage; Elisabeth S. Bakker; Savanna C. Barry; S. Tatiana Becker; Enrique Bethel; James G. Douglass; Hannah J. van Duijnhoven; Jimmy de Fouw; Thomas K. Frazer; et al. (Global Change Biology, 2025)
Climate‐driven shifts in herbivores, temperature, and nutrient runoff threaten coastal ecosystem resilience. However, ecological resilience, particularly for foundation species, remains poorly understood due to the scarcity of field experiments conducted across appropriate spatial and temporal scales that investigate multiple stressors. This study evaluates the resilience of a widespread tropical marine plant (turtlegrass) to disturbances across its geographic range and examines how environmental gradients in (a)biotic factors influence recovery. We assessed turtlegrass resilience by following recovery rates for a year after a simulated pulse disturbance (complete above‐ and belowground biomass removal). Contrary to studies in temperate areas, higher temperature generally enhanced seagrass recovery. While nutrients had minimal individual effects, they reduced aboveground recovery when combined with high levels of herbivore grazing (meso and megaherbivore). Belowground recovery was also affected by combined high levels of nutrients and grazing (megaherbivores only). Light availability had minimal effects. Our results suggest that the resilience of some tropical species, particularly in cooler subtropical waters, may initially benefit from warming. However, continuing shifts in nutrient supply and changes in grazing pressure may ultimately serve to compromise seagrass recovery.

Connectivity conservation to mitigate climate and land-cover change impacts on Borneo - Matthew J. Struebig; Moritz Wenzler; Rebecca K. Runting; Elizabeth Law; Sugeng Budiharta; David Seaman; Stephanie Kramer-Schadt (Biological Conservation, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Process Implementation of In-house Prepared Blenderized Feeds Administered Enterally in the Inpatient Setting - S. Gomez-Rubio; K. Kramer; R. Nuse Tome (Journal of the Academy of Nutrition and Dietetics, 2024)

Potential landscape connectivity for invasive wild pigs (Sus scrofa) across the northern prairies of North America - Corey J. Kramer; Melanie R. Boudreau; Ryan Powers; Kurt C. VerCauteren; Ryan S. Miller; Ryan K. Brook (Biological Invasions, 2024)

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Phytoplankton composition from sPACE: Requirements, opportunities, and challenges - Ivona Cetinić; Cecile S. Rousseaux; Ian T. Carroll; Alison P. Chase; Sasha J. Kramer; P. Jeremy Werdell; David A. Siegel; Heidi M. Dierssen; Dylan Catlett; Aimee Neeley; Inia M. Soto Ramos; Jennifer L. Wolny; et al. (Remote Sensing of Environment, 2024)

Landscape-scale population trends in the occurrence and abundance of wildlife populations using long term camera-trapping data - Joshua P. Twining; David Kramer; Kelly A. Perkins; Angela K. Fuller (Biological Conservation, 2024)

Analysis of an optical imaging system prototype for autonomously monitoring zooplankton in an aquaculture facility - M.N. Bowman; R.A. McManamay; A. Rodriguez Perez; G. Hamerly; W. Arnold; E. Steimle; K. Kramer; B. Norris; D. Prangnell; M. Matthews (Aquacultural Engineering, 2024)

Validation of global ionospheric models using long-term observations of pulsar Faraday rotation with the LOFAR radio telescope - Nataliya K. Porayko; Maaijke Mevius; Manuel Hernández-Pajares; Caterina Tiburzi; German Olivares Pulido; Qi Liu; Joris P. W. Verbiest; Jörn Künsemöller; Moochickal Ambalappat Krishnakumar; Ann-Sofie Bak Nielsen; Marcus Brüggen; Victoria Graffigna; et al. (Journal of Geodesy, 2023)
Broad band pulsar radiation can be effectively used to monitor the properties of the magneto-ionic media through which it propagates. Faraday rotation calculated from polarised pulsar observations provides an integrated product of electron densities and the line-of-sight component of the magnetic field in the intervening plasma. In particular, a time-variable effect mainly associated with the rapidly changing column density of the Earth’s ionosphere and plasmasphere heavily dominates the observed Faraday rotation of pulsar radiation. In this work, we aim to carry out a performance test of three GNSS-based models of the ionosphere using observations of PSR J0332+5434 taken with the LOw Frequency ARray (LOFAR). As it was shown in Porayko et al. (Month Not Roy Astron Soc 483(3):4100–4113, 2019. https://doi.org/10.1093/mnras/sty3324 . arXiv:1812.01463 ), the conventional single layer model (SLM), which assumes that the ionosphere is a thin slab at a fixed effective height, is not capable of fully accounting for the ionospheric Faraday rotation in pulsar data. The simplified physics of the SLM is upgraded within IRI-Plas (International Reference Ionosphere and Plasmasphere) extended SLM and the dual-layer voxel TOmographic Model of the Ionosphere (TOMION), both of which partially account for the thickness and vertical dynamics of the terrestrial plasma. Although the last two improve the reconstruction of the ionospheric Faraday rotation, none of the considered models completely purge the observed residual variations. With this study, we show that the long term LOFAR observations of Faraday rotation of pulsars provide an excellent tool to test and improve models of the magneto-ionic content of the Earth’s atmosphere.

Observing ocean ecosystem responses to volcanic ash - K.M. Bisson; S. Gassó; N. Mahowald; S. Wagner; B. Koffman; S.A. Carn; S. Deutsch; E. Gazel; S. Kramer; N. Krotkov; C. Mitchell; M.E. Pritchard; et al. (Remote Sensing of Environment, 2023)

P22-12: Mucus hyper secretion in Bronchus-on-a-Chip as the airway remodeling indication - A. Mori; M. Vermeer; S. Ito; W. Strijker; B. Kramer; A. Nicolas; K. Ohashi; K. Matsumura; S. Muratani; T. Sekine (Toxicology Letters, 2023)

OS01-06: Development and characterization of Bronchus-on-a-Chip in a novel microfluidic platform suitable for air exposure - W. Strijker; A. Mori; M. Vermeer; S. Ito; K. Ohashi; K. Matsumura; S. Muratani; T. Sekine; A. Nicolas; B. Kramer (Toxicology Letters, 2023)

Towards a better future for biodiversity and people: Modelling Nature Futures - HyeJin Kim; Garry D. Peterson; William W.L. Cheung; Simon Ferrier; Rob Alkemade; Almut Arneth; Jan J. Kuiper; Sana Okayasu; Laura Pereira; Lilibeth A. Acosta; Rebecca Chaplin-Kramer; Eefje den Belder; et al. (Global Environmental Change, 2023)

Identification of phthalate mixture exposure targets in the human and mouse ovary in vitro - Ilari Tarvainen; Delia A. Soto; Mary J. Laws; Richelle D. Björvang; Anastasios Damdimopoulos; Kristine Roos; Tianyi Li; Stav Kramer; Zhong Li; Darja Lavogina; Nadja Visser; Theodora K. Kallak; et al. (Reproductive Toxicology, 2023)

Seagrass Abundance Predicts Surficial Soil Organic Carbon Stocks Across the Range of Thalassia testudinum in the Western North Atlantic - James W. Fourqurean; Justin E. Campbell; O. Kennedy Rhoades; Calvin J. Munson; Johannes R. Krause; Andrew H. Altieri; James G. Douglass; Kenneth L. Heck; Valerie J. Paul; Anna R. Armitage; Savanna C. Barry; Enrique Bethel; et al. (Estuaries and Coasts, 2023)

Exploring the potential of theory-based evaluation to strengthen marine spatial planning practice - Rachel Zuercher; Nicole Motzer; Natalie C. Ban; Wesley Flannery; Anne D. Guerry; Rafael A. Magris; Shauna L. Mahajan; Ana K. Spalding; Vanessa Stelzenmüller; Jonathan G. Kramer (Ocean & Coastal Management, 2023)

Comparison of DRASTIC and DRASTICL groundwater vulnerability assessments of the Burdekin Basin, Queensland, Australia - Nasrin Taghavi; Robert K. Niven; Matthias Kramer; David J. Paull (Science of The Total Environment, 2023)

Estimating population changes in humpback whales Megaptera novaeangliae migrating past Cape Vidal, South Africa - C Wilkinson; E Seyboth; J Olbers; E Vermeulen; R Kramer; K Findlay (African Journal of Marine Science, 2023)

Reactive diving and sprinting performances in soccer goalkeepers improved by caffeine consumption and post-activation performance enhancement - J. Impey; K. Bahdur; M. Kramer (German Journal of Exercise and Sport Research, 2022)

Multiple Functional Brain Networks Related to Pain Perception Revealed by fMRI - Matteo Damascelli; Todd S. Woodward; Nicole Sanford; Hafsa B. Zahid; Ryan Lim; Alexander Scott; John K. Kramer (Neuroinformatics, 2022)
The rise of functional magnetic resonance imaging (fMRI) has led to a deeper understanding of cortical processing of pain. Central to these advances has been the identification and analysis of “functional networks”, often derived from groups of pre-selected pain regions. In this study our main objective was to identify functional brain networks related to pain perception by examining whole-brain activation, avoiding the need for a priori selection of regions. We applied a data-driven technique—Constrained Principal Component Analysis for fMRI (fMRI-CPCA)—that identifies networks without assuming their anatomical or temporal properties. Open-source fMRI data collected during a thermal pain task (33 healthy participants) were subjected to fMRI-CPCA for network extraction, and networks were associated with pain perception by modelling subjective pain ratings as a function of network activation intensities. Three functional networks emerged: a sensorimotor response network, a salience-mediated attention network, and the default-mode network. Together, these networks constituted a brain state that explained variability in pain perception, both within and between individuals, demonstrating the potential of data-driven, whole-brain functional network techniques for the analysis of pain imaging data.

Corrigendum: Phytoplankton Growth and Productivity in the Western North Atlantic: Observations of Regional Variability From the NAAMES Field Campaigns - James Fox; Michael J. Behrenfeld; Nils Haëntjens; Alison Chase; Sasha J. Kramer; Emmanuel Boss; Lee Karp-Boss; Nerissa L. Fisher; W. Bryce Penta; Toby K. Westberry; Kimberly H. Halsey (Frontiers in Marine Science, 2021)

Applying the zoo model to conservation of threatened exceptional plant species - Jordan Wood; Jonathan D. Ballou; Taylor Callicrate; Jeremie B. Fant; M. Patrick Griffith; Andrea T. Kramer; Robert C. Lacy; Abby Meyer; Sara Sullivan; Kathy Traylor‐Holzer; Seana K. Walsh; Kayri Havens (Conservation Biology, 2020)
Maintaining a living plant collection is the most common method of ex situ conservation for plant species that cannot be seed banked (i.e., exceptional species). Viability of living collections, and their value for future conservation efforts, can be limited without coordinated efforts to track and manage individuals across institutions. Using a pedigree‐focused approach, the zoological community has established an inter‐institutional infrastructure to support long‐term viability of captive animal populations. We assessed the ability of this coordinated metacollection infrastructure to support the conservation of 4 plant species curated in living collections at multiple botanic gardens around the world. Limitations in current practices include the inability to compile, share, and analyze plant collections data at the individual level, as well as difficulty in tracking original provenance of ex situ material. The coordinated metacollection framework used by zoos can be adopted by the botanical community to improve conservation outcomes by minimizing the loss of genetic diversity in collections. We suggest actions to improve ex situ conservation of exceptional plant species, including developing a central database to aggregate data and track unique individuals of priority threatened species among institutions and adapting a pedigree‐based population management tool that incorporates life‐history aspects unique to plants. If approached collaboratively across regional, national, and global scales, these actions could transform ex situ conservation of threatened plant species.

Body mass and cardiorespiratory fitness are associated with altered brain metabolism - Ryan J. Larsen; Lauren B. Raine; Charles H. Hillman; Arthur F. Kramer; Neal J. Cohen; Aron K. Barbey (Metabolic Brain Disease, 2020)

Human variability in isoform-specific UDP-glucuronosyltransferases: markers of acute and chronic exposure, polymorphisms and uncertainty factors - E. E. J. Kasteel; K. Darney; N. I. Kramer; J. L. C. M. Dorne; L. S. Lautz (Archives of Toxicology, 2020)
UDP-glucuronosyltransferases (UGTs) are involved in phase II conjugation reactions of xenobiotics and differences in their isoform activities result in interindividual kinetic differences of UGT probe substrates. Here, extensive literature searches were performed to identify probe substrates (14) for various UGT isoforms (UGT1A1, UGT1A3, UGT1A4, UGT1A6, UGT1A9, UGT2B7 and UGT2B15) and frequencies of human polymorphisms. Chemical-specific pharmacokinetic data were collected in a database to quantify interindividual differences in markers of acute (Cmax) and chronic (area under the curve, clearance) exposure. Using this database, UGT-related uncertainty factors were derived and compared to the default factor (i.e. 3.16) allowing for interindividual differences in kinetics. Overall, results show that pharmacokinetic data are predominantly available for Caucasian populations and scarce for other populations of different geographical ancestry. Furthermore, the relationships between UGT polymorphisms and pharmacokinetic parameters are rarely addressed in the included studies. The data show that UGT-related uncertainty factors were mostly below the default toxicokinetic uncertainty factor of 3.16, with the exception of five probe substrates (1-OH-midazolam, ezetimibe, raltegravir, SN38 and trifluoperazine), with three of these substrates being metabolised by the polymorphic isoform 1A1. Data gaps and future work to integrate UGT-related variability distributions with in vitro data to develop quantitative in vitro–in vivo extrapolations in chemical risk assessment are discussed.

Phytoplankton Growth and Productivity in the Western North Atlantic: Observations of Regional Variability From the NAAMES Field Campaigns - James Fox; Michael J. Behrenfeld; Nils Haëntjens; Alison Chase; Sasha J. Kramer; Emmanuel Boss; Lee Karp-Boss; Nerissa L. Fisher; W. Bryce Penta; Toby K. Westberry; Kimberly H. Halsey (Frontiers in Marine Science, 2020)
The ability to quantify spatio-temporal variability in phytoplankton growth and productivity is essential to improving our understanding of global carbon dynamics and trophic energy flow. Satellite-based observations offered the first opportunity to estimate depth-integrated net primary production (NPP) at a global scale, but early modeling approaches could not effectively address variability in algal physiology, particularly the effects of photoacclimation on changes in cellular chlorophyll. Here, a previously developed photoacclimation model was used to derive depth-resolved estimates of phytoplankton division rate (μ) and NPP. The new approach predicts NPP values that closely match discrete measurements of 14 C-based NPP and effectively captured both spatial and temporal variability observed during the four field campaigns of the North Atlantic Aerosols and Marine Ecosystems Study (NAAMES). We observed favorable growth conditions for phytoplankton throughout the annual cycle in the subtropical western North Atlantic. As a result, high rates of μ are sustained year-round resulting in a strong coupling between growth and loss processes and a more moderate spring bloom compared to the high-latitude subarctic region. Considerable light limitation was observed in the subarctic province during the winter, which resulted in divergent growth dynamics, stronger decoupling from grazing pressure and a taxonomically distinct phytoplankton community. This study demonstrates how detailed knowledge of phytoplankton division rate furthers our understanding of global carbon cycling by providing insight into the resulting influence on phytoplankton taxonomy and the loss processes that dictate the fate of fixed carbon.

Similar factors underlie tree abundance in forests in native and alien ranges - Masha T. van der Sande; Helge Bruelheide; Wayne Dawson; Jürgen Dengler; Franz Essl; Richard Field; Sylvia Haider; Mark van Kleunen; Holger Kreft; Joern Pagel; Jan Pergl; Oliver Purschke; et al. (Global Ecology and Biogeography, 2020)
Aim Alien plant species can cause severe ecological and economic problems, and therefore attract a lot of research interest in biogeography and related fields. To identify potential future invasive species, we need to better understand the mechanisms underlying the abundances of invasive tree species in their new ranges, and whether these mechanisms differ between their native and alien ranges. Here, we test two hypotheses: that greater relative abundance is promoted by (a) functional difference from locally co‐occurring trees, and (b) higher values than locally co‐occurring trees for traits linked to competitive ability. Location Global. Time period Recent. Major taxa studied Trees. Methods We combined three global plant databases: sPlot vegetation‐plot database, TRY plant trait database and Global Naturalized Alien Flora (GloNAF) database. We used a hierarchical Bayesian linear regression model to assess the factors associated with variation in local abundance, and how these relationships vary between native and alien ranges and depend on species’ traits. Results In both ranges, species reach highest abundance if they are functionally similar to co‐occurring species, yet are taller and have higher seed mass and wood density than co‐occurring species. Main conclusions Our results suggest that light limitation leads to strong environmental and biotic filtering, and that it is advantageous to be taller and have denser wood. The striking similarities in abundance between native and alien ranges imply that information from tree species’ native ranges can be used to predict in which habitats introduced species may become dominant.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Robustness of trait connections across environmental gradients and growth forms - Habacuc Flores‐Moreno; Farideh Fazayeli; Arindam Banerjee; Abhirup Datta; Jens Kattge; Ethan E. Butler; Owen K. Atkin; Kirk Wythers; Ming Chen; Madhur Anand; Michael Bahn; Chaeho Byun; et al. (Global Ecology and Biogeography, 2019)
Aim Plant trait databases often contain traits that are correlated, but for whom direct (undirected statistical dependency) and indirect (mediated by other traits) connections may be confounded. The confounding of correlation and connection hinders our understanding of plant strategies, and how these vary among growth forms and climate zones. We identified the direct and indirect connections across plant traits relevant to competition, resource acquisition and reproductive strategies using a global database and explored whether connections within and between traits from different tissue types vary across climates and growth forms. Location Global. Major taxa studied Plants. Time period Present. Methods We used probabilistic graphical models and a database of 10 plant traits (leaf area, specific leaf area, mass‐ and area‐based leaf nitrogen and phosphorous content, leaf life span, plant height, stem specific density and seed mass) with 16,281 records to describe direct and indirect connections across woody and non‐woody plants across tropical, temperate, arid, cold and polar regions. Results Trait networks based on direct connections are sparser than those based on correlations. Land plants had high connectivity across traits within and between tissue types; leaf life span and stem specific density shared direct connections with all other traits. For both growth forms, two groups of traits form modules of more highly connected traits; one related to resource acquisition, the other to plant architecture and reproduction. Woody species had higher trait network modularity in polar compared to temperate and tropical climates, while non‐woody species did not show significant differences in modularity across climate regions. Main conclusions Plant traits are highly connected both within and across tissue types, yet traits segregate into persistent modules of traits. Variation in the modularity of trait networks suggests that trait connectivity is shaped by prevailing environmental conditions and demonstrates that plants of different growth forms use alternative strategies to cope with local conditions.

Cerebrospinal Fluid from Patients with Sporadic Amyotrophic Lateral Sclerosis Induces Degeneration of Motor Neurons Derived from Human Embryonic Stem Cells - Rajendrarao Sumitha; Venkataswamy M. Manjunatha; Rajesh K. Sabitha; Phalguni A. Alladi; A. Nalini; Laxmi T. Rao; B. K. Chandrasekhar Sagar; Harry W. M. Steinbusch; Boris W. Kramer; T. N. Sathyaprabha; Trichur R. Raju (Molecular Neurobiology, 2019)

Erratum to: Comparison of in vitro test systems using bacterial and mammalian cells for genotoxicity assessment within the health-related indication value (HRIV) concept - Eva-Maria Prantl; Meike Kramer; Carsten K. Schmidt; Martina Knauer; Stefan Gartiser; Aliaksandra Shuliakevich; Julia Milas; Hansruedi Glatt; Walter Meinl; Henner Hollert (Environmental Science and Pollution Research, 2018)

Comparison of in vitro test systems using bacterial and mammalian cells for genotoxicity assessment within the “health-related indication value (HRIV) concept - Eva-Maria Prantl; Meike Kramer; Carsten K. Schmidt; Martina Knauer; Stefan Gartiser; Aliaksandra Shuliakevich; Julia Milas; Hansruedi Glatt; Walter Meinl; Henner Hollert (Environmental Science and Pollution Research, 2018)

Correction to : Coordinate expression of pan-neuronal and functional signature genes in sympathetic neurons - U. Ernsberger; M. Kramer; K. Tsarovina; T. Deller; H. Rohrer (Cell and Tissue Research, 2018)

Coordinate expression of pan-neuronal and functional signature genes in sympathetic neurons - U. Ernsberger; M. Kramer; K. Tsarovina; T. Deller; H. Rohrer (Cell and Tissue Research, 2017)

A global synthesis of the effects of diversified farming systems on arthropod diversity within fields and across agricultural landscapes - Elinor M. Lichtenberg; Christina M. Kennedy; Claire Kremen; Péter Batáry; Frank Berendse; Riccardo Bommarco; Nilsa A. Bosque‐Pérez; Luísa G. Carvalheiro; William E. Snyder; Neal M. Williams; Rachael Winfree; Björn K. Klatt; et al. (Global Change Biology, 2017)
Agricultural intensification is a leading cause of global biodiversity loss, which can reduce the provisioning of ecosystem services in managed ecosystems. Organic farming and plant diversification are farm management schemes that may mitigate potential ecological harm by increasing species richness and boosting related ecosystem services to agroecosystems. What remains unclear is the extent to which farm management schemes affect biodiversity components other than species richness, and whether impacts differ across spatial scales and landscape contexts. Using a global metadataset, we quantified the effects of organic farming and plant diversification on abundance, local diversity (communities within fields), and regional diversity (communities across fields) of arthropod pollinators, predators, herbivores, and detritivores. Both organic farming and higher in‐field plant diversity enhanced arthropod abundance, particularly for rare taxa. This resulted in increased richness but decreased evenness. While these responses were stronger at local relative to regional scales, richness and abundance increased at both scales, and richness on farms embedded in complex relative to simple landscapes. Overall, both organic farming and in‐field plant diversification exerted the strongest effects on pollinators and predators, suggesting these management schemes can facilitate ecosystem service providers without augmenting herbivore (pest) populations. Our results suggest that organic farming and plant diversification promote diverse arthropod metacommunities that may provide temporal and spatial stability of ecosystem service provisioning. Conserving diverse plant and arthropod communities in farming systems therefore requires sustainable practices that operate both within fields and across landscapes.

Repellency of the Origanum onites L. essential oil and constituents to the lone star tick and yellow fever mosquito - John F. Carroll; Betul Demirci; Matthew Kramer; Ulrich R. Bernier; Natasha M. Agramonte; K. Husnu Can Baser; Nurhayat Tabanca (Natural Product Research, 2017)

Dynamic soil characterization and site response estimation for Erbaa, Tokat (Turkey) - Muge K. Akin; Steven L. Kramer; Tamer Topal (Natural Hazards, 2016)

The geology of the Matala Dome: an important piece of the Pan-African puzzle in Central Zambia - K. V. Naydenov; J. Lehmann; K. Saalmann; L. Milani; J. Poterai; J. A. Kinnaird; G. Charlesworth; J. D. Kramers (International Journal of Earth Sciences, 2016)

Importance sampling for efficient modelling of hydraulic loads in the Rhine–Meuse delta - F. L. M. Diermanse; K. M. De Bruijn; J. V. L. Beckers; N. L. Kramer (Stochastic Environmental Research and Risk Assessment, 2015)

Amphiphilic triblock copolymers with PEGylated hydrocarbon structures as environmentally friendly marine antifouling and fouling-release coatings - Zhaoli Zhou; David R. Calabrese; Warren Taylor; John A. Finlay; Maureen E. Callow; James A. Callow; Daniel Fischer; Edward J. Kramer; Christopher K. Ober (Biofouling, 2014)

The third dimension of bat migration: evidence for elevational movements of Miniopterus natalensis along the slopes of Mount Kilimanjaro - Christian C. Voigt; Maria Helbig-Bonitz; Stephanie Kramer-Schadt; Elisabeth K. V. Kalko (Oecologia, 2014)

A newly developed seismic microzonation model of Erbaa (Tokat, Turkey) located on seismically active eastern segment of the North Anatolian Fault Zone (NAFZ) - Muge K. Akin; Tamer Topal; Steven L. Kramer (Natural Hazards, 2013)

TRY – a global database of plant traits - J. KATTGE; S. DÍAZ; S. LAVOREL; I. C. PRENTICE; P. LEADLEY; G. BÖNISCH; E. GARNIER; M. WESTOBY; P. B. REICH; I. J. WRIGHT; J. H. C. CORNELISSEN; C. VIOLLE; et al. (Global Change Biology, 2011)
Plant traits – the morphological, anatomical, physiological, biochemical and phenological characteristics of plants and their organs – determine how primary producers respond to environmental factors, affect other trophic levels, influence ecosystem processes and services and provide a link from species richness to ecosystem functional diversity. Trait data thus represent the raw material for a wide range of research from evolutionary biology, community and functional ecology to biogeography. Here we present the global database initiative named TRY, which has united a wide range of the plant trait research community worldwide and gained an unprecedented buy‐in of trait data: so far 93 trait databases have been contributed. The data repository currently contains almost three million trait entries for 69 000 out of the world's 300 000 plant species, with a focus on 52 groups of traits characterizing the vegetative and regeneration stages of the plant life cycle, including growth, dispersal, establishment and persistence. A first data analysis shows that most plant traits are approximately log‐normally distributed, with widely differing ranges of variation across traits. Most trait variation is between species (interspecific), but significant intraspecific variation is also documented, up to 40% of the overall variation. Plant functional types (PFTs), as commonly used in vegetation models, capture a substantial fraction of the observed variation – but for several traits most variation occurs within PFTs, up to 75% of the overall variation. In the context of vegetation models these traits would better be represented by state variables rather than fixed parameter values. The improved availability of plant trait data in the unified global database is expected to support a paradigm shift from species to trait‐based ecology, offer new opportunities for synthetic plant trait research and enable a more realistic and empirically grounded representation of terrestrial vegetation in Earth system models.

Fluorine-free mixed amphiphilic polymers based on PDMS and PEG side chains for fouling release applications - Harihara S. Sundaram; Youngjin Cho; Michael D. Dimitriou; Craig J. Weinman; John A. Finlay; Gemma Cone; Maureen E. Callow; James A. Callow; Edward J. Kramer; Christopher K. Ober (Biofouling, 2011)

Fine-scale spatial and temporal population genetics of Aedes japonicus , a new US mosquito, reveal multiple introductions - D. M. FONSECA; A. K. WIDDEL; M. HUTCHINSON; S.-E. SPICHIGER; L. D. KRAMER (Molecular Ecology, 2010)

Assessment of current rates of Diadema antillarum larval settlement - M. W. Miller; K. L. Kramer; S. M. Williams; L. Johnston; A. M. Szmant (Coral Reefs, 2009)

Recruitment failure in Florida Keys Acropora palmata, a threatened Caribbean coral - D. E. Williams; M. W. Miller; K. L. Kramer (Coral Reefs, 2008)

The role of adherent cells in the immunosuppressed state of mouse progeny transplacentally exposed to benzo(α)pyrene - Paul Urso; Mary K. Kramer (In Vitro Cellular & Developmental Biology - Animal, 2008)

Inhibition of neutral endopeptidase potentiates neutrophil activation during Mg-deficiency in the rat - I. T. Mak; J. H. Kramer; J. J. Chmielinska; M. H. Khalid; K. M. Landgraf; W. B. Weglicki (Inflammation Research, 2008)

Alternative methods to safety studies in experimental animals: role in the risk assessment of chemicals under the new European Chemicals Legislation (REACH) - W. Lilienblum; W. Dekant; H. Foth; T. Gebel; J. G. Hengstler; R. Kahl; P.-J. Kramer; H. Schweinfurth; K.-M. Wollin (Archives of Toxicology, 2008)

A refined radio-telemetry technique to monitor right ventricle or pulmonary artery pressures in rats: a useful tool in pulmonary hypertension research - M. L. Handoko; I. Schalij; K. Kramer; A. Sebkhi; P. E. Postmus; W. J. van der Laarse; W. J. Paulus; A. Vonk-Noordegraaf (Pflügers Archiv - European Journal of Physiology, 2008)

Regional Advection Perturbations in an Irrigated Desert (RAPID) experiment - H. A. R. De Bruin; O. K. Hartogensis; R. G. Allen; J. W. J. L. Kramer (Theoretical and Applied Climatology, 2005)

Evaluation of six process‐based forest growth models using eddy‐covariance measurements of CO 2 and H 2 O fluxes at six forest sites in Europe - K. Kramer; I. Leinonen; H. H. Bartelink; P. Berbigier; M. Borghetti; Ch Bernhofer; E. Cienciala; A. J. Dolman; O. Froer; C. A. Gracia; A. Granier; T. Grünwald; et al. (Global Change Biology, 2002)
Reliable models are required to assess the impacts of climate change on forest ecosystems. Precise and independent data are essential to assess this accuracy. The flux measurements collected by the EUROFLUX project over a wide range of forest types and climatic regions in Europe allow a critical testing of the process‐based models which were developed in the LTEEF project. The ECOCRAFT project complements this with a wealth of independent plant physiological measurements. Thus, it was aimed in this study to test six process‐based forest growth models against the flux measurements of six European forest types, taking advantage of a large database with plant physiological parameters. The reliability of both the flux data and parameter values itself was not under discussion in this study. The data provided by the researchers of the EUROFLUX sites, possibly with local corrections, were used with a minor gap‐filling procedure to avoid the loss of many days with observations. The model performance is discussed based on their accuracy, generality and realism. Accuracy was evaluated based on the goodness‐of‐fit with observed values of daily net ecosystem exchange, gross primary production and ecosystem respiration (gC m −2 d −1 ), and transpiration (kg H 2 O m −2 d −1 ). Moreover, accuracy was also evaluated based on systematic and unsystematic errors. Generality was characterized by the applicability of the models to different European forest ecosystems. Reality was evaluated by comparing the modelled and observed responses of gross primary production, ecosystem respiration to radiation and temperature. The results indicated that: Accuracy . All models showed similar high correlation with the measured carbon flux data, and also low systematic and unsystematic prediction errors at one or more sites of flux measurements. The results were similar in the case of several models when the water fluxes were considered. Most models fulfilled the criteria of sufficient accuracy for the ability to predict the carbon and water exchange between forests and the atmosphere. Generality. Three models of six could be applied for both deciduous and coniferous forests. Furthermore, four models were applied both for boreal and temperate conditions. However, no severe water‐limited conditions were encountered, and no year‐to‐year variability could be tested. Realism. Most models fulfil the criterion of realism that the relationships between the modelled phenomena (carbon and water exchange) and environment are described causally. Again several of the models were able to reproduce the responses of measurable variables such as gross primary production (GPP), ecosystem respiration and transpiration to environmental driving factors such as radiation and temperature. Stomatal conductance appears to be the most critical process causing differences in predicted fluxes of carbon and water between those models that accurately describe the annual totals of GPP, ecosystem respiration and transpiration. As a conclusion, several process‐based models are available that produce accurate estimates of carbon and water fluxes at several forest sites of Europe. This considerable accuracy fulfils one requirement of models to be able to predict the impacts of climate change on the carbon balance of European forests. However, the generality of the models should be further evaluated by expanding the range of testing over both time and space. In addition, differences in behaviour between models at the process level indicate requirement of further model testing, with special emphasis on modelling stomatal conductance realistically.

Molecular mapping of the Oregon Wolfe Barleys: a phenotypically polymorphic doubled-haploid population - J. M. Costa; A. Corey; P. M. Hayes; C. Jobet; A. Kleinhofs; A. Kopisch-Obusch; S. F. Kramer; D. Kudrna; M. Li; O. Riera-Lizarazu; K. Sato; P. Szucs; et al. (Theoretical and Applied Genetics, 2001)

Novel histaprodifen analogues as potent histamine H 1 -receptor agonists in the pithed and in the anaesthetized rat - Schlicker E.; Kozłowska H.; Kwolek G.; Malinowska B.; Kramer K.; Pertz H.; Elz S.; Schunack W. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2001)

Carbon dynamics within agricultural and native sites in the loess region of western Iowa - K. L. Manies; J. W. Harden; L. Kramer; W. J. Parton (Global Change Biology, 2001)
In order to quantify the historical changes in carbon storage that result from agricultural conversion, this study compared the carbon dynamics of two sites in the loess region of Iowa: a native prairie and a cropland. Field data were obtained to determine present‐day carbon storage and its variability within a landscape (a stable ridgetop vs. eroding upper‐midslope vs. depositional lower slope). Models were used to recreate the historical carbon budget of these sites and determine the cropland's potential to be a net CO 2 source or sink, relative to the atmosphere. Regardless of slope position, the cropland site contains approximately half the amount of carbon as prairie. Variability in soil carbon storage within a site as a consequence of slope position is as large or larger (variations of 200–300%) than temporal variation (∼200% at all slope positions). The most extreme difference in soil carbon storage between the cropland and prairie sites is found in the soil at the upper‐midslope, which is the area of greatest erosion. The models estimate that 93–172% of the carbon in the original topsoil has been lost from the cropland's eroding midslope. Much of this carbon is derived from deeper soil horizons. Either a small sink or strong source of carbon to the atmosphere is created, depending on the fate of the eroded sediment and its associated carbon.

The importance of phenology for the evaluation of impact of climate change on growth of boreal, temperate and Mediterranean forests ecosystems: an overview - K. Kramer; I. Leinonen; D. Loustau (International Journal of Biometeorology, 2000)

Absorption, metabolism and excretion of a single oral dose of 14 C-repaglinide during repaglinide multiple dosing - P. N. M. van Heiningen; V. Hatorp; K. Kramer Nielsen; K. T. Hansen; J. J. van Lier; N. C. De Merbel; B. Oosterhuis; J. H. G. Jonkman (European Journal of Clinical Pharmacology, 1999)

Abstracts of Papers presented at a Workshop on Ecology of Botrytis and Sclerotinia and their Interaction With Other Microorganisms Abstracts of Papers Presented at a Workshop on Genetic Aspects ofFusarium oxysporum and Related Species Abstracts of Papers and Discussion Contributions Presented at the Dutch-Israeli (Diarp) Workshop on Environment-Friendly Crop Protection of the Flower Industry to Suit Future Market Trends - A. Ten Have; W. Oude Breuil; J. Wubben; W. Mulder; J. Visser; J. van Kan; T. Quidde; P. Tudzynski; T. M. O’Neill; G. De Meyer; K. Audenaert; J. Bigirimana; et al. (Phytoparasitica, 1999)

Human calicivirus genogroup II capsid sequence diversity revealed by analyses of the prototype Snow Mountain agent - M. E. Hardy; S. F. Kramer; J. J. Treanor; M. K. Estes (Archives of Virology, 1997)

The mode of action of primycin - I. Horvth; M. Kramer; P. I. Bauer; K. G. Bki (Archives of Microbiology, 1979)